(untitled) (LEARNing Landscapes, 2014)
Drawing on her lived experiences, and using the metaphor of a Snakes and Ladders game, the author reflects on her teacher practice related to using an inquiry approach in her French Immersion Kindergarten classroom. Looking backward while moving forward in time, she makes visible her process of change, foregrounding how her beliefs about children, teaching, and learning—her educational philosophy—paired with a new understanding of learning theories—in particular, constructivism—shape a pedagogical approach centered in inquiry-based learning. She stories her move from being structured and teacher-directed in her pedagogical approach to embracing an emergent curriculum and a student-centered pedagogy.